Cryofreezing of Grass Carp (Ctenopharyngodon idella) Spermatozoa for Ex Situ Conservation (Progressive Agriculture, 2013)
Experiments were conducted to develop and standardize the protocols for cryopreservation of sperm of grass carp (Ctenopharyngodon idella). Seven extenders such as Alsevers solution, Urea egg-yolk, Egg-yolk citrate, Kurokura- 1, Kurokura-2, 0.9% NaCl and 0.6% Glucose and five cryoprotectants i.e. DMSO, methanol, ethanol, DMA and glycerol were employed for finding suitable combinations. Cryodiluents were prepared by mixing the cryoprotectants at 10% concentration of the extenders (v/v). Milt and cryodiluents were mixed at a ratio of 1:9 for Alsevers solution, Kurokura-1, Kurokura-2, 0.9% NaCl and 0.6% glucose, and 1:4 for urea egg-yolk and egg-yolk citrate. Among the 35 combinations of extenders and cryoprotectants, Alsevers solution with ethanol and methanol, urea egg-yolk and egg-yolk citrate with DMSO found suitable for preservation and it produced 74 ± 2.44%, 72 ± 2.54%, 76 ± 2.44% and 75 ± 2.23% spermatozoan motility at the post-thaw period respectively. Rest of the combinations, on the other hand, produced 75%) and 1:4 with urea eggyolk and egg-yolk citrate (>70%). As an optimum level of cryoprotectant, 10% concentration was found effective to produce significantly highest (P